Predeployment of Transponders for Dynamic Lightpath Provisioning in Translucent Spectrally–Spatially Flexible Optical Networks - Krzysztof Walkowiak; Mirosław Klinkowski; Adam Włodarczyk; Andrzej Kasprzak (Applied Sciences, 2020)
We consider a dynamic lightpath provisioning problem in translucent spectrally–spatially flexible optical networks (SS-FONs) in which flexible signal regeneration is achieved with transponders operating in back-to-back (B2B) configurations. In the analyzed scenario, an important aspect that has a significant impact on the network performance is the decision on placement of transponders that can be used for two purposes: transmitting/receiving (add/drop) of optical signals at the source/destination nodes and regeneration of the signals at some intermediate nodes. We propose a new algorithm called scaled average used regenerators (SAUR). The key idea of the SAUR method is based on a data analytics approach, i.e., the algorithm exploits information on network traffic characteristics and the applied dynamic routing algorithm to obtain additional knowledge for the decision on transponder placement. The numerical results obtained for two representative topologies highlight that the proposed SAUR method outperforms reference algorithms in terms of the amount of traffic that can be accepted in the network. In other words, placement of transponders yielded by the SAUR method allows to increase the SS-FON throughput using only the existing resources, i.e., the network operator does not have to invest in new devices or fibers.